Interfacial engineered iron oxide nanoring for T2-weighted magnetic resonance imaging-guided magnetothermal-chemotherapy - Bao, Jianfeng; Tu, Hui; Li, Jing; Dong, Yanbo; Dang, Le; Yurievna, Korjova Elena; Zhang, Fengshou; Xu, Lei (Frontiers in Bioengineering and Biotechnology, 2022)
Due to no penetration depth limitation, low cost, and easy control, magnetic nanoparticles mediated magnetic hyperthermia therapy (MHT) has shown great potential in experimental and clinal treatments of various diseases. However, the low heating conversion efficiencies and short circulation times are major drawback for most existing magnetic-thermal materials. Additionally, single MHT treatment always leads to resistance and recurrence. Herein, a highly efficient magnetic-thermal conversion, ferrimagnetic vortex nanoring Fe3O4 coated with hyaluronic acid (HA) nanoparticles (Fe3O4@HA, FVNH NPs) was firstly constructed. Additionally, the doxorubicin (DOX) was successfully enclosed inside the FVNH and released remotely for synergetic magnetic–thermal/chemo cancer therapy. Due to the ferrimagnetic vortex-domain state, the ring shape Fe3O4 displays a high specific absorption rate (SAR) under an external alternating magnetic field (AMF). Additionally, antitumor drug (DOX) can be encapsulated inside the single large hole of FVNH by the hyaluronic acid (HA) shell and quickly released in response the tumor acidic microenvironments and AMF. What’s more, the non-loaded FVNH NPs show good biocompatibility but high cytotoxicity after loading DOX under AMF. Furthermore, the synthesized FVNH can efficiently reduce the transverse relaxation time and enhance negative magnetic resonance imaging (MRI). The impressive in vivo systemic therapeutic efficacy of FVNH was also proved in this work. Taken together, the results of this study demonstrate that the synthesized FVNH NPs offer the promise of serving as multifunctional theranostic nanoplatforms for medical imaging-guided tumor therapies.